New mtDNA data reveal a wide distribution of the Japanese ginbuna Carassius langsdorfii in Europe. Issue 2 (29th November 2012) - Kalous, L.; Rylková, K.; Bohlen, J.; Šanda, R.; Petrtýl, M.
<x xml:space="preserve">Abstract</x> In this study, records on the occurrence of the Japanese ginbuna Carassius langsdorfii from northern Germany, north‐western Italy and southern Bosnia and Herzegovina are presented. The new findings, in addition to former studies reported in the Czech Republic and Greece, show that C. langsdorfii is much more widespread in Europe than was previously believed.